Martial mechanics : maximum results with minimum effort in the practice of martial arts - Starr, Phillip (Berkeley, Calif. : Blue Snake Books, North Atlantic Books, 2008)
'Martial Mechanics describes the principles upon which traditional martial arts techniques are based, explaining how laws of physics and principles of Kinesiology affect techniques and how one can utilize these laws to make techniques faster, more powerful, and more effective in combat'--Provided by publisher.
Includes bibliographical references
Keywords: Martial arts; Martial arts -- Study and teaching